2021
DOI: 10.1039/d1cy00433f
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of the side-chain mechanism of the MTO process over H-SSZ-13 using DFT and ab initio calculations

Abstract: The side-chain mechanism of the methanol-to-olefins process over the H-SSZ-13 acidic zeolite was investigated using periodic density functional theory with corrections from highly accurate ab intio calculations on large cluster models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 112 publications
1
22
0
Order By: Relevance
“…Previous computational investigations on H-SAPO-34, 19,27,46 H-ZSM-5 21 and H-SSZ-13 49 have shown that the side-chain mechanism has a clear kinetic selectivity for ethylene. These investigations, however, have also shown that the rate-limiting step, the methylation of the side chain, is relatively high with computed activation free energies on the order of 190 kJ mol −1 or higher as determined by us for H-SSZ-13 57 and by others for H-SAPO-34, 49,58 H-ZSM-5, 58 H-BEA 58 and H-ZSM-22. 58 We note here that in our qualitative discussion of barrier heights, we always refer to Gibbs free energies and to the highest barrier encountered in the catalytic cycle relative to the lowest preceding intermediate, thus giving the largest 'span' as described nicely in the energetic span model.…”
Section: Introductionmentioning
confidence: 77%
“…Previous computational investigations on H-SAPO-34, 19,27,46 H-ZSM-5 21 and H-SSZ-13 49 have shown that the side-chain mechanism has a clear kinetic selectivity for ethylene. These investigations, however, have also shown that the rate-limiting step, the methylation of the side chain, is relatively high with computed activation free energies on the order of 190 kJ mol −1 or higher as determined by us for H-SSZ-13 57 and by others for H-SAPO-34, 49,58 H-ZSM-5, 58 H-BEA 58 and H-ZSM-22. 58 We note here that in our qualitative discussion of barrier heights, we always refer to Gibbs free energies and to the highest barrier encountered in the catalytic cycle relative to the lowest preceding intermediate, thus giving the largest 'span' as described nicely in the energetic span model.…”
Section: Introductionmentioning
confidence: 77%
“…It is now widely accepted that the complex reaction network taking place within the small-pore, cages/cavities of MTO catalysts, following an initial induction period, proceeds through a dual-cycle mechanism that comprises of olefins-based chemistries of successive methylation and cracking steps and aromatic-based chemistries of methylation and dealkylation [4,5,[8][9][10][35][36][37][38][39][40][41][42][43][44]. The two cycles are connected through hydrogen transfer and cyclization events.…”
Section: Introductionmentioning
confidence: 99%
“…We computed free energies as described in previous work. 55 A hexagonal unit cell with pre-optimized parameters (a = 13.625 Å, c = 15.067 Å) and one Brønsted acid site per unit cell was used for H-SSZ-13, see ESI † for locations of bulkier transition structures within the cavities. Structures were optimized employing periodic density functional theory (DFT) calculations with the dispersion-corrected PBE-D3 71,72 density functional (zero damping) using the VASP code with the standard PAWs [73][74][75] and an energy cutoff of 400 eV.…”
Section: Methodsmentioning
confidence: 99%
“…[40][41][42][43][44][45][46][47][48][49] For instance, Alexopoulos et al have shown that a reaction path analysis of EtOH dehydration from free energy profiles should include the effect of reaction conditions, feed concentrations and conversion levels. While DFT and ab initio post-Hartree-Fock (HF) calculations have been used extensively for MTO and related processes, 13,14,41,45,48,[50][51][52][53][54][55] theoretical insight into the analogous conversion of EtOH in acidic zeolites has so far mostly been limited to EtOH dehydration to ethene and DEE 26,[56][57][58] and is rather scarce for subsequent propagation steps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation